Effect of flexible work environment on employee job satisfaction of Nepalese commercial banks - Thapa, Sweta Sanyasee (Nepalese Journal of Management, 2024)
This study examines the effect of flexible work environment on employee job satisfaction in Nepalese commercial banks. Employee satisfaction is the dependent variable. The selected independent variables are flexible work environment, telecommuting, work shifting, organizational culture, employee training and job sharing. The primary source of data is used to assess the opinions of the respondents regarding different factors affecting employee job satisfaction in Nepalese commercial banks. The study is based on primary data with 121 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of flexible work environment, telecommuting, work shifting, organizational culture, employee training and job sharing on employee job satisfaction in Nepalese commercial banks. The study showed that flexible work environment has a positive impact on employee job satisfaction. It implies that providing flexible work environment leads to employee job satisfactions. Likewise, telecommuting has a positive impact on employee job satisfaction. This means that facility of telecommuting leads to the employee job satisfaction. Similarly, work shifting has a positive impact on employee job satisfaction. It indicates that the work shifting provided by Nepalese commercial banks leads to increase in employee job satisfaction. Moreover, organizational culture has a positive impact on employee job satisfaction. It implies that proper and supportive organizational culture leads to increase in employee job satisfaction. Likewise, employee training has a positive impact on employee job satisfaction indicating that training and developments provided by the banks to their employees leads to increase in employee job satisfaction. However, job sharing has a negative impact on employee satisfaction. It indicates that practices of job sharing in the organization leads to decrease employee job satisfaction.